Influence of bodybuilding classes on physical qualities of the qualified sportswomen in different phases of the specific biological cycle - Мулик, Вячеслав; Джим, Євгенія (Slobozhanskyi Herald of Science and Sport, 2017)
Vyacheslav Mulik & Evgeniya Dzhim Purpose: to conduct researches of influence of classes of the sportswomen who are going in for bodybuilding and fitness-bikini on manifestation of physical qualities in different phases of the ovarian-menstrual cycle. Material & Methods: researches were conducted in sports fitness-clubs of Kharkov "Feromon", "Gorod", “King” with the qualified sportswomen who are going in for bodybuilding and fitness-bikini within 3 months of the preparatory period in number of 14 people. We used as methods of the research: the analysis of references and testing of level of motive qualities in separate phases of OMC. Results: the theoretical analysis of features of the accounting of phases of OMC at sportswomen is submitted and the testing of the level of development of physical qualities in different phases of the specific biological cycle at the qualified sportswomen, who are going in for bodybuilding, is held. Conclusions: the received results demonstrate that physical efficiency of the qualified sportswomen, who are going in for bodybuilding, is not identical in phases of the ovarian-menstrual cycle. It is revealed that the best conditions for performance of considerable exercise stresses in post-ovulatory and post-menstrual phases of OMC, therefore it is expedient to plan them in the preparatory periods of the qualified sportswomen, who are going in for bodybuilding.